Penerapan Metode Al-Kamal dalam Meningkatkan Kemampuan Baca Kitab di MTs Mambaul Ulum Paiton – Probolinggo - Pratama, Delvin (Maliki Interdisciplinary Journal, 2024)
Reading is part of the learning process that has existed for a long time and has become the heart of various educational institutions. The process of increasing knowledge in humans mostly occurs because it is caused by one’s reading and literature abilities. Reading in the learning process is like being a bridge for someone to cross the world of knowledge in order to add insight and knowledge. In the process, many types of books and scriptures were written by various scientists and scholars who later became important guides for present and future generations. These books and scriptures were written not only in one language, but in many languages ​​from around the world. For students who live in Islamic boarding schools, studying ancient Arabic books is like a basic necessity in the learning process. Many methods are used in learning to read and analyze various existing books, one of which is the Al-Kamal Method. The Al-Kamal method is a method of reading Arabic books used at the Mambaul Ulum Islamic Boarding School. The existence of this method is expected to make it easier for students to improve their ability to read books at Islamic boarding schools. This study aims to find out how the application of the Al-Kamal method in improving reading skills at MTs Mambaul Ulum Paiton. The method used in this study is a qualitative method based on class action, interviews, direct observation and others. This research was conducted as a foundation in learning Arabic and the ability to read books at MTs Mambaul Ulum and its integration with the teaching and learning process.